Aging amorphous/crystalline heterophase PdCu nanosheets for catalytic reactions. Issue 5 (5th July 2019) - Cheng, Hongfei; Yang, Nailiang; Liu, Xiaozhi; Yun, Qinbai; Goh, Min Hao; Chen, Bo; Qi, Xiaoying; Lu, Qipeng; Chen, Xiaoping; Liu, Wen; Gu, Lin; Zhang, Hua
ABSTRACT: Phase engineering is arising as an attractive strategy to tune the properties and functionalities of nanomaterials. In particular, amorphous/crystalline heterophase nanostructures have exhibited some intriguing properties. Herein, the one-pot wet-chemical synthesis of two types of amorphous/crystalline heterophase PdCu nanosheets is reported, in which one is amorphous phase-dominant and the other one is crystalline phase-dominant. Then the aging process of the synthesized PdCu nanosheets is studied, during which their crystallinity increases, accompanied by changes in some physicochemical properties. As a proof-of-concept application, their aging effect on catalytic hydrogenation of 4-nitrostyrene is investigated. As a result, the amorphous phase-dominant nanosheets initially show excellent chemoselectivity. After aging for 14 days, their catalytic activity is higher than that of crystalline phase-dominant nanosheets. This work demonstrates the intriguing properties of heterophase nanostructures, providing a new platform for future studies on the regulation of functionalities and applications of nanomaterials by phase engineering.